Design of digital signal processing system using TMS32010 for application as band-pass equalizer, echo generator and equalizer doubler - 264900 Wei, Chuan Beng (Kuala Lumpur : UTM, 1989)
Thesis (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1988